Z+35=11

Simple and best practice solution for Z+35=11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Z+35=11 equation:


Simplifying
Z + 35 = 11

Reorder the terms:
35 + Z = 11

Solving
35 + Z = 11

Solving for variable 'Z'.

Move all terms containing Z to the left, all other terms to the right.

Add '-35' to each side of the equation.
35 + -35 + Z = 11 + -35

Combine like terms: 35 + -35 = 0
0 + Z = 11 + -35
Z = 11 + -35

Combine like terms: 11 + -35 = -24
Z = -24

Simplifying
Z = -24

See similar equations:

| -y^2+7y-9=0 | | Z-26=-44 | | (x-5)(x^2-2x-7)= | | b*2+2b=0 | | x^3+3x^2-81x-243= | | 5u+14=-10u-2 | | 5u=10u-2 | | -0.01x^2+.7x+6.1= | | 8=(n)/(-7)-5 | | 3/4x-15=30 | | 3.6+10m=6.41 | | 0.5x+4=13.5 | | 6x+20=14-52 | | Y^2-9y+74=0 | | 120+18m=408 | | 34n-120=390 | | (3x/7y^3)^2 | | 5x=x+30(5) | | (2x^3y^3-3xy+4)(4xy^3)=z | | g(x)=x^2-12x+39 | | 6y-4y^2=-7 | | 10n+6=9 | | 4x^4-23x^2-6=0 | | 14x=108 | | 6x^4-23x^2-6=0 | | -11=8w-11 | | -46=5x-.333 | | 2x-36=26 | | -4x-4x=52-4 | | 25x-8x+2=0 | | n(n-3)=180 | | y^2-y-1=0 |

Equations solver categories